Friedrich Engels and Marxist Economic Theory - Hutchison, T. W. (Journal of Political Economy, 1978)
This is a review article based on W. O. Henderson's two-volume Life of Friedrich Engels. After a brief biographical summary, Engels's contributions to political economy are examined, and it is suggested that these are much more important than has so far been recognized (e.g., by Schumpeter). In particular, Engels's paper "Outlines of a Critique of Political Economy" announced several of the basic and least invalid themes of Marxist political economy. Later Engels, when criticizing Utopian socialism, contributed a very remarkable account of the essential functions of the competitive price mechanism.